2015
DOI: 10.3109/19390211.2015.1008615
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Supplemental Citrulline-Malate Ingestion on Blood Lactate, Cardiovascular Dynamics, and Resistance Exercise Performance in Trained Males

Abstract: Citrulline-malate (CM) has been proposed to provide an ergogenic effect during resistance exercise; however, there is a paucity of research investigating these claims. Therefore, we investigated the impact that CM supplementation would have on repeated bouts of resistance exercise. Fourteen resistance-trained males participated in a randomized, counterbalanced, double-blind study. Subjects were randomly assigned to placebo (PL) or CM (8 g) and performed three sets each of chin-ups, reverse chin-ups, and push-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
6
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 33 publications
3
67
6
4
Order By: Relevance
“…Previous studies have demonstrated the positive ergogenic effects of l -citrulline supplementation in anaerobic exercise [14,15]. In this way, l -citrulline-malate supplementation (8 g) increased submaximal resistance exercise performance (60–80% 1RM) [16,17], decreased rating of perceived exertion (RPE) [4], and increased the heart rate (HR) response [18]. In addition, watermelon juice (1.2 g of l -citrulline) and enriched watermelon juice (6 g l -citrulline) were reported as decreasing muscle soreness after 24 h of exercise [19].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the positive ergogenic effects of l -citrulline supplementation in anaerobic exercise [14,15]. In this way, l -citrulline-malate supplementation (8 g) increased submaximal resistance exercise performance (60–80% 1RM) [16,17], decreased rating of perceived exertion (RPE) [4], and increased the heart rate (HR) response [18]. In addition, watermelon juice (1.2 g of l -citrulline) and enriched watermelon juice (6 g l -citrulline) were reported as decreasing muscle soreness after 24 h of exercise [19].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was reported that 8 g of CM might be useful to increase athletic performance in high-intensity anaerobic exercise of flat barbell bench presses and to relieve post-exercise muscle soreness in males 17) . Furthermore, 8 g of CM before repeated bouts of lower and upper-body resistance exercise significantly increased the amount of repetitions performed by trained males 18,32) . Similarly, in female participants, acute 8-g CM supplementation prior to 1 h of upper and lower-body submaximal weightlifting exercise increased the performance and decreased the RPE during upper-body exercise 19) .…”
Section: Discussionmentioning
confidence: 88%
“…Arginine is noted for its unique benefits in improving reproductive, cardiovascular, pulmonary, renal, gastrointestinal, liver, and immune functions . Also, recent studies have proposed that citrulline enhances exercise endurance and performance in healthy adults . The beneficial effects of citrulline may stem from improvements in the arginine/nitric oxide pathway.…”
Section: Discussionmentioning
confidence: 99%
“…18 Also, recent studies have proposed that citrulline enhances exercise endurance and performance in healthy adults. 20,21 The beneficial effects of citrulline may stem from improvements in the arginine/nitric oxide pathway. Citrulline ingestion increases endothelial nitric oxide synthesis and may improve endothelial function.…”
Section: Discussionmentioning
confidence: 99%